Electrically induced soft actuators based on thermoplastic polyurethane and their actuation performances including tiny force measurement. (10th October 2019) - Li, Chongchao; Xia, Hong; Yao, Juming; Ni, Qing-Qing
Abstract: Many gel-like soft composites were obtained by using thermoplastic polyurethane (TPU) as the matrix in this work. Different contents of plasticizer dibutyl adipate (DBA) was added to TPU to swell its molecular chains and allowed them to pass through each other easily. These samples were then sandwiched between two electrodes as actuators and their actuation abilities were investigated. The results showed that the largest deflection among those samples was up to 12.11 mm, which corresponds to 48.44% of the length of samples (at 2.86 V μm −1 ). The deflection increased with increasing of the electric field intensity. Besides, the actuator was able to promptly respond to the change of voltage within 0.12 s. A wide response ability in the frequency region from 0.5 Hz to 10 Hz was confirmed, and the largest amplitude over 22 mm of the actuator was observed at 5 Hz. Furthermore, a new method was proposed in this paper to estimate the tiny force generated by the actuator. The small variation (less than 3%) of the measured results indicated that the proposed method is reliable even at a small bending angle. It is believed that the rapid bending capability and large deformation of the developed actuator at low intensity of electric field will make its considerable contributions to the field of soft robotics or biomaterials. Graphical abstract: Image 1 Highlights: Plasticized gel based actuators were prepared and their properties were investigated. The largest actuating deflection was up to 48.44% of the sample length at 2.86 V μm −1 The actuation behaviors in an electric field is a consequence of multiple factors. A new method was proposed to estimate the tiny actuation force.